Raziskovanje čarovništva na terenu. Čarovništvo kot večplasten verovanjski sistem Researching Witchcraft on the Field. Witchcraft as a Complex System of Belief - Mencej, Mirjam (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The article is based on fieldwork material on witchcraft that was collected in a rural part of western Slovenia between 2000 and 2002. The author tried to emphasize the complexity of withcraft as well as the fact that there are different categories of »witches« in this area. Emphasized is the need to consider all aspects of witchcraft. Equally necessary is that a researcher of this phenomenon be able to recognize numerous differences and nuances and that he or she considers the dynamics of their overlapping. The second part of the article focuses on posible disturbances in communication and on false interpretations that may be the result of ignoring different aspects and types of witchcraft and witches.